INTEGRATION OF SUSTAINABLE AGRICULTURE CONCEPT AND LOCAL ECOLOGICAL KNOWLEDGE IN SHIFTING CULTIVATION FARMING SYSTEM, REVIEW OF ENVIRONMENTAL ANTHROPOLOGY STUDY - Yohanes Kamakaula; Yunita Palinggi (Yayasan Adra Karima Hubbi, 2025)
Shifting cultivation systems are often considered unsustainable practices, yet many indigenous communities have developed this agricultural model ecologically and socially. In this context, it is important to review how local ecological knowledge plays a role in shaping sustainable agricultural systems and how the integration of sustainable agriculture concepts can strengthen these local practices. This study aims to explore the relationship between sustainable agricultural principles and local ecological practices in shifting cultivation, using an environmental anthropology approach. The main focus is to explore the meaning, values, and strategies of traditional agriculture as part of an adaptive social-ecological system. The research method used is qualitative ethnographic with participatory observation techniques, in-depth interviews, and case studies in shifting cultivation farming communities in the interior. The results of the study show that the shifting cultivation system contains the principles of diversification, land rotation, ecological control based on customary norms, and spiritual values towards nature. This system has indirectly created ecological and social sustainability without the intervention of modern technology. The conclusion of this study confirms that sustainability does not always have to be constructed through a technocratic approach, but can be built through recognition of local ecological practices.